EFFECTS OF KEFIR SUPPLEMENTATION ON BODY ANTIOXIDANT-SYSTEMS, HAEMOLYMPH HEAT-SHOCK PROTEIN 70 AND TRYPSIN, IN THE CRAYFISH ASTACUS LEPTODACTYLUS ESCHSCHOLTZ (DECAPODA, ASTACIDEA) - Aksu, Onder; Turkoglu, Semra; Can, Erkan; Erisir, Mine; Kocabas, Mehmat; Kayim, Murathan; Benzer, Fulya (Brill, 2022)
This study was designed to investigate the effects of dietary kefir on trypsin, heat shock protein 70 (HSP70) as well as the oxidant and antioxidant status of the freshwater crayfish, Astacus leptodactylus. The experiment was performed with the four following treatments: Control group, D1, D2 and D3 (kefir supplemented diet 2, 4, 8 g/kg of crayfish body mass, respectively). Crayfish were stocked into 12 fibreglass tanks (three replicates per treatment) and fed for 45 days. Reduced glutathione (GSH), glutathione peroxidase (GSH-Px), malondialdehyde (MDA) and catalase (CAT) in hepatopancreas and muscle were analysed to determine the status of the oxidant/antioxidant balance. In addition, HSP70 and trypsin were measured in haemolymph. Our results indicated that the activity of GSH-Px, MDA and GSH levels decreased in hepatopancreas (p>0.05) and muscle tissues (p <0.05) with increasing kefir concentration, while CAT activity increased (p <0.05). Trypsin and HSP70 insignificantly decreased in haemolymph.
Keywords: Antioxidant enzymes; Astacus leptodactylus; kefir; trypsin; HSP70